2017
DOI: 10.1111/1462-2920.13844
|View full text |Cite
|
Sign up to set email alerts
|

The FgSRP1 SR‐protein gene is important for plant infection and pre‐mRNA processing in Fusarium graminearum

Abstract: The versatile functions of SR (serine/arginine-rich) proteins in pre-mRNA splicing and processing are modulated by reversible phosphorylation. Previous studies showed that FgPrp4, the only protein kinase among spliceosome components, is important for intron splicing and the FgSrp1 SR protein is phosphorylated at five conserved sites in Fusarium graminearum. In this study, we showed that the Fgsrp1 deletion mutant rarely produced conidia and caused only limited symptoms on wheat heads and corn silks. Deletion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 80 publications
(123 reference statements)
1
29
0
Order By: Relevance
“…For selfing, the tub1 mutant and complementation strains were inoculated on carrot agar plates and fertilized as described (Luo et al ., ). Perithecium formation, cirrhi production and the formation of asci and ascospores were examined 7–14 days post‐fertilization (dpf) (Zhang et al ., ). For thick sections, 7‐dpf perithecia were fixed in 4% (v v −1 ) glutaraldehyde and dehydrated in a gradient concentration of acetone solution before being embedded in Spurr resin as described (Cao et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…For selfing, the tub1 mutant and complementation strains were inoculated on carrot agar plates and fertilized as described (Luo et al ., ). Perithecium formation, cirrhi production and the formation of asci and ascospores were examined 7–14 days post‐fertilization (dpf) (Zhang et al ., ). For thick sections, 7‐dpf perithecia were fixed in 4% (v v −1 ) glutaraldehyde and dehydrated in a gradient concentration of acetone solution before being embedded in Spurr resin as described (Cao et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…After streaking ascospore suspensions on 3% (w v −1 ) water agar, ascospores with morphological defects were isolated by dragging individual ascospores under an inverse microscopy. Single ascospore cultures were then assayed for defects in growth and sexual reproduction as described (Luo et al ., ) (Zhang et al ., ). To identify RIP mutations in ascospore progeny normal in growth but defective in ascosporogenesis, the endogenous TUB1 gene was amplified with primers Tub1‐S1 and Tub1‐155/R (Supporting Information Table S1) and sequenced.…”
Section: Methodsmentioning
confidence: 97%
“…One example is the RNA‐binding protein Rbp35, which harbours an N‐terminal RRM and six RGG repeats involved in the alternative pre‐mRNA 3′‐end splicing of target genes that control mycelial growth, infection‐related development and pathogenicity in M. oryzae (Franceschetti et al ., ). Recently, studies have reported that a serine/arginine‐rich protein, FgSrp1 and a protein kinase, FgPrp4, both play important roles in the pre‐mRNA splicing process, and are essential for mycelial growth and pathogenicity in F. graminearum (Gao et al ., ; Y. Zhang et al ., ). Another study reported that Srk1 participates in the developmental stages of vegetative growth, sexual reproduction, and plant infection and is also required for pre‐mRNA AS and gene expression in F. graminearum (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The FgSnu66 CT50 ‐3xFLAG and FgSnu66 N596 ‐GFP fusion constructs were generated by the yeast gap repair approach (Zhou et al, ) and co‐transformed into the wild‐type strain PH‐1. Total proteins were isolated from transformants expressing both FgSnu66 CT50 ‐3xFLAG and FgSnu66 N596 ‐GFP constructs and incubated with anti‐GFP beads (Sigma‐Aldrich, St. Louis, MO) as described (Hou et al, , Zhang et al, ). Western blots of total proteins and proteins eluted from anti‐GFP beads were detected with the anti‐GFP (Roche, USA) and anti‐FLAG (Sigma‐Aldrich, USA) antibodies as described (Liu et al, ).…”
Section: Methodsmentioning
confidence: 99%